Critical Discourse Analysis on Reconstruction of the Mediation Process of Judges Based on Maslahat at the Palopo Religious Court - Abdul Kadir; Mustaming; Abdain (Universitas Islam Negeri Palopo, 2025)
This study examines the reconstruction of judicial mediation processes through the lens of critical discourse analysis, focusing on the implementation of maslahat principles at the Palopo Religious Court. The research investigates how Islamic jurisprudential concepts of maslahat (public interest/benefit) can be integrated into contemporary judicial mediation practices to enhance conflict resolution effectiveness within the Indonesian religious court system. Using critical discourse analysis methodology, this study analyzes the linguistic patterns, power dynamics, and ideological frameworks embedded in judicial mediation discourse at the Palopo Religious Court. The research explores how judges construct meaning through language while incorporating maslahat-based approaches in their mediation processes, examining both explicit and implicit discursive strategies that shape dispute resolution outcomes. The findings reveal significant opportunities for reconstructing mediation processes by systematically integrating maslahat principles into judicial discourse. The analysis demonstrates how judges can employ maslahat-oriented language and reasoning to facilitate more culturally relevant and ethically grounded mediation sessions. The study identifies key discursive patterns that either support or hinder the effective application of maslahat in judicial mediation contexts. The research contributes to understanding how Islamic legal principles can be meaningfully incorporated into modern judicial practices through careful attention to discursive construction. The reconstruction model proposed emphasizes the importance of aligning judicial language with maslahat values to achieve more equitable and contextually appropriate dispute resolution outcomes. This study provides practical insights for religious court judges seeking to enhance their mediation practices through maslahat-based approaches while maintaining procedural integrity within the Indonesian legal system. The findings suggest that critical discourse analysis offers valuable tools for understanding and improving the integration of Islamic jurisprudential principles in contemporary judicial mediation processes.